The Effect Of Liquid Organic Fertilizer Leaves Of Moringa (Moringa Oleifera L.) With Banana Peel (Musa Paradisiaca L.) On Generative Growth Of Cayenne Pepper (Capsicum Frutescens L. Var. Pelita 8) - Fijannati Fijannati; Wardiah Wardiah; Hafnati Rahmatan; Supriatno Supriatno; Muhibbuddin Muhibbuddin (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2022)
Cayenne pepper (Capsicum frutescens L.) is an important and widely cultivated agricultural commodity in Indonesia. Cayenne pepper has a specific aroma, taste and color, so it is widely used by the community as a spice and seasoning for cooking. Generally, farmers use chemical fertilizers to increase soil fertility, but the use of chemical fertilizers will have a negative impact on the environment and humans. The purpose of this study was to determine the effect and optimal concentration of liquid organic fertilizer mixture of Moringa leaves and kepok banana peels on the generative growth of cayenne pepper. This study uses a quantitative approach and experimental research types. The research design used was a completely randomized design (CRD) with 4 treatments, namely P0 (control), P1 (10%), P2 (20%), and P3 (30%). Data were analyzed using Analysis of Variance (ANAVA) and Follow-Up Test with Significantly Significant Differences (BNJ) at a significant level of 0.05. The results showed that the application of a mixture of liquid organic fertilizers of Moringa leaves and kepok banana peels had a significant effect on the generative growth of cayenne pepper for the wet weight parameter of the fruit and the optimal treatment was at a concentration of 20%. The conclusion of this study is that a mixture of liquid organic fertilizer from kelor leaves and kepok banana peels has an effect on increasing the generative growth of cayenne pepper.Keywords: cayenne pepper, moringa, kepok banana peel, generative.Cabai rawit (Capsicum frutescens L.) adalah komoditas pertanian yang penting dan banyak dibudidayakan di Indonesia. Cabai rawit memiliki aroma, rasa dan warna yang spesifik, sehingga banyak digunakan oleh masyarakat sebagai rempah dan bumbu masakan. Umumnya petani menggunakan pupuk kimia untuk menambah kesuburan tanah, namun penggunaan pupuk kimia akan berdampak negatif bagi lingkungan dan manusia. Tujuan penelitian ini adalah untuk mengetahui pengaruh dan konsentrasi optimal campuran pupuk organik cair daun kelor dan kulit pisang kepok terhadap pertumbuhan generatif cabai rawit. Penelitian ini menggunakan pendekatan kuantitatif dan jenis penelitian eksperimen. Rancangan penelitian yang digunakan adalah Rancangan Acak Lengkap (RAL) dengan 4 perlakuan, yaitu P0 (kontrol), P1 (10%), P2 (20%), dan P3 (30%). Data dianalisis menggunakan Analisis Varian (ANAVA) dan Uji Lanjut Beda Nyata Jujur (BNJ) pada taraf signifikan 0,05. Hasil penelitian menunjukkan pemberian campuran pupuk organik cair daun kelor dan kulit pisang kepok berpengaruh nyata tehadap pertumbuhan generatif cabai rawit untuk parameter berat basah buah dan perlakuan optimal terdapat pada konsentrasi 20%. Simpulan dari penelitian ini adalah campuran pupuk organik cair daun kelor dan kulit pisang kepok berpengaruh dalam meningkatkan pertumbuhan generatif cabai rawit.Kata kunci: cabai rawit, kelor, kulit pisang kepok, generatif